Assessing the Impact of Financial Resource Management Challenges on Competency Based Education Implementation in Public Junior Schools in Baringo County - Tallam, Maldrine Jemutai; Kiplangat, Henry K.; Ngala, Fredrick B. J. A. (My University, 2025)
Abstract The study assessed the impact of financial resource management constraints on the implementation of Competency Based Education (CBE) in public junior schools in Baringo County, Kenya. The shift to CBE in Kenya demanded effective financial planning, budgeting, and resource allocation to sustain learner-centered approaches. However, schools in rural and resource-limited contexts such as Baringo County experienced challenges that hindered smooth implementation. The study adopted a descriptive research design guided by positivist philosophy, targeting 1,739 respondents, including head teachers, junior school teachers, and sub-county directors. A sample of 317 respondents was selected using stratified random sampling. Data were collected through structured questionnaires and semi-structured interviews, and analyzed using both descriptive and inferential statistics, complemented by thematic analysis for qualitative data. The findings revealed that inadequate financial planning, delayed fund disbursement, weak accountability systems, and poor budget prioritization significantly affected the provision of instructional materials, teacher training, and infrastructural development required for CBE. Regression analysis indicated a strong relationship between financial resource management practices and effective curriculum implementation. The study concluded that strengthening financial management capacity and timely funding are essential for successful CBE implementation. It recommended enhanced budgetary oversight, capacity building for school managers, and strategic government support to ensure sustainable financing of CBE reforms
Full text
Keywords: Financial resource management; Competency-based education; Implementation challenges; Baringo County; educational financing.